Bonding by Self-Propagating Reaction - Fisher, David (Materials Research Foundations Ser., 2019)
Bonding by Self-Propagating Reaction represents a highly promising approach for the joining of dissimilar materials in such fields as microelectronics, infrared sensors, micro-electro-mechanical systems (MEMS), aerospace and nuclear industries, and surface engineering for chemical, mechanical and microsystems applications. Keywords: Microsystems, Sensors, Actuators, High-Temperature Synthesis, Multilayer Films, Bilayer Thickness, Magnetron Sputtering, Thermite-Type Bonding, Silicon Wafers, Intermetallics, Metalloids, Metallic Glasses, Ceramics, Metallized Ceramics, Nanofoils, Nanocomposite Foi.